Knockout Mouse Models for Peroxiredoxins - Young Jae Lee (Antioxidants, 2020)
Peroxiredoxins (PRDXs) are members of a highly conserved peroxidase family and maintain intracellular reactive oxygen species (ROS) homeostasis. The family members are expressed in most organisms and involved in various biological processes, such as cellular protection against ROS, inflammation, carcinogenesis, atherosclerosis, heart diseases, and metabolism. In mammals, six PRDX members have been identified and are subdivided into three subfamilies: typical 2-Cys (PRDX1, PRDX2, PRDX3, and PRDX4), atypical 2-Cys (PRDX5), and 1-Cys (PRDX6) subfamilies. Knockout mouse models of PRDXs have been developed to investigate their in vivo roles. This review presents an overview of the knockout mouse models of PRDXs with emphases on the biological and physiological changes of these model mice.